Model Hidrodinamika Tiga-Dimensi (3-D) Arus Pasang Surut di Laut Jawa - Nining Sari Ningsih (Institut Teknologi Bandung, 1998)
A three-dimensional coastal ocean circulation model is developed by employing the splitting method to reduce the large amount of computational work as one of the major problems related to three-dimensional model. The mode splitting technique splits the three-dimensional model into vertically integrated equations (external mode) and three-dimensional equations (internal mode). In further considerations the transformation of the governing equations from z-coordinate to a dimensionless vertical coordinate (Ï) was performed to achieve a better simulation of both the surface and bottom mixed layers. The developed model is verified by comparing the simulation results in an idealized channel with those of POM (the Princeton Ocean Model). Then, the model is applied for simulating tidal currents in Java Sea.